Tailoring properties of natural deep eutectic solvents with water to facilitate their applications - Dai, Yuntao; Witkamp, Geert-Jan; Verpoorte, Robert; Choi, Young Hae (Food chemistry, 2015)
Previously it was demonstrated that natural deep eutectic solvents (NADES) are promising green solvents for the extraction of natural products. However, despite their potential, an obvious disadvantage of NADES is the high viscosity. Here we explored the dilution effect on the structures and physicochemical properties of NADES and their improvements of applications using quercetin and carthamin. The results of FT-IR and (1)H NMR experiments demonstrated that there are intensive H-bonding interactions between the two components of NADES and dilution with water caused the interactions weaken gradually and even disappeared completely at around 50% (v/v) water addition. A small amount of water could reduce the viscosity of NADES to the range of water and increase the conductivity by up to 100 times for some NADES. This study provides the basis for modulating NADES in a controllable way for their applications in food processing, enzyme reactions, pharmaceuticals and cosmetics.